Kajian Rekayasa Lalu Lintas Pasca Dibangunnya Fly Over Kemiling, Bandar Lampung - Latifah, Asmaul; Putra, Sasana; Herianto, Dwi (Universitas Lampung, 2019)
Congestion has become a common problem faced by the community. The intersection of Pramuka -Cik Ditiro street is one of the most prone congestion areas in Bandar Lampung. One of the solution that can we do to reduce congestion is to build a fly over,that is expected to reduce congestion so that it will give a good impacts. The purpose of this study is to determine traffic conflicts and the magnitude of travel delays occurring around the Kemiling fly over. This study uses gap acceptance and follow-up methods to calculate the queue of vehicles that rotate at u-turn. The data collection is done by recording a video. The duration of the recording are 4 times with a duration of 1.5 hours in the morning and evening for 2 days (Monday and Saturday). Based on data analysis that has been carried out, after the construction of a fly over, it turns out there are still some congestion conflicts at several points during rush hour (morning and evening). The data obtained is the delay on the u-turn in front of the fly over which is 8.42 seconds for the average gap time and 5.13 seconds for the average follow-up time with the number of vehicles passing as many as 274. Therefore to solving the problem a roundabout being planned with a diameter of 20 m. Keywords: Fly Over, U-Turn, Follow-Up, Gap Acceptance, Roundabout.